2007
DOI: 10.1002/j.0022-0337.2007.71.11.tb04414.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Weight and Dental Caries Among Pediatric Patients in an Urban Dental School? A Correlation Study

Abstract: Obesity in the young is a public health priority. The prevalence of overweight children in the United States has risen almost threefold in the last two decades. An association between weight and oral health has been suggested in adults, whereas evidence supporting this association in children is controversial at best. The aim of our study was to evaluate the association between weight and dental caries in a random prospective cohort of children at their initial visit at an urban dental school. One hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 21 publications
3
32
1
3
Order By: Relevance
“…Dental caries is a multifactorial infectious disease. Factors affecting the onset of lesions include oral hygiene, diet composition and consumption frequency, socioeconomic status, salivary immunoglobulins, bacterial load and fluoride intake (1,2,7,14). The exploration of the link between anthropometric measurements and oral health in children has been controversial (5,16,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries is a multifactorial infectious disease. Factors affecting the onset of lesions include oral hygiene, diet composition and consumption frequency, socioeconomic status, salivary immunoglobulins, bacterial load and fluoride intake (1,2,7,14). The exploration of the link between anthropometric measurements and oral health in children has been controversial (5,16,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining such data is important for evaluating underweight, stunting, wasting or overweight associated with increased risk for adverse health outcomes (3). Information regarding the association between underweight/obesity and dental caries is inconclusive (4)(5)(6)(7)(8). Some cross-sectional studies have shown a positive association between obesity and dental caries (4,8), while another study has reported a weak or no association between body mass index (BMI) and dental caries (6).…”
Section: Introductionmentioning
confidence: 99%
“…29 The studies exploring the relationship between caries experience and BMI reported conflicting results. 6,[18][19][20] The present study was undertaken to explore the relationship between BMI and dental caries prevalence among schoolchildren aged 12 to 15 years in Mangaluru city in South India. The etiology of childhood obesity is multifactorial and includes social and cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…9-13 A study by Bailleul-Forestier et al 14 assessed caries experience in an adolescent population being treated for severe obesity and found that there was a significant association between body mass index (BMI) and decayed, missing, and filled teeth (DMFT) in the severely obese group. Furthermore, Hilgers et al 15 and Willershausen et al [16][17][18] reported an association between increased weight and high caries frequency in children and adolescents, while Macek and Mitola, 19 Pinto et al, 20 and Kopycka-Kedzierawski et al 21 found no significant association between weight and caries. In most of these studies, dental caries recordings were performed by oral examination and diagnosed at caries level.…”
Section: Original Researchmentioning
confidence: 99%
“…The prevalence of dental caries was reported to be 89.8% in Yasuj (Iran) and 79.7% in Ardabil (Iran) [8,9]. Obesity and overweight have also been major public health problems in the past 20 years [10,11]. The prevalence of obesity is increasing worldwide in all age groups and nationalities [10,12].…”
Section: Introductionmentioning
confidence: 99%